Accessible education: designing the educational environment for sustainable development - Dziatkovskaya, Elena N.; Dlimbetova, Gaini K.; Dziatkovsky, Anton D. (Journal of the Belarusian State University. Ecology, 2022)
The problem of achieving accessible and quality education set by the Global Action Programme on Education for Sustainable Development (2014) is discussed. It reveals the connection between accessibility of education and making it inclusive in its broadest sense, as education for all. The author hypothesizes that many of the difficulties that arise in the organization of inclusive education could be eliminated at the stage of designing the educational environment. The requests of modern pedagogy for educational environments of general education are analyzed and it is concluded that they do not fully reflect the interests of inclusive education. The aim of the study was to the principles of designing an accessible educational environment of general education organizations that implement inclusion. The general and special approaches to designing an accessible educational environment in conditions of inclusion were considered. The role of health-saving and developing character of the educational environment, and also its cultural and natural appropriateness to provide accessibility of education for all students as subjects of educational activity and subjects of health is grounded.
Keywords: educational environment; inclusion; accessibility; adaptability